Migration of Muslims to Other Parts of the World: New Events and Facts - Maulidizen, Ahmad; Tirmidzi, Mamduh; Rizapoor, Habiburrahman (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The issues surrounding Migration and the Problems of Muslim Minorities in the Modern World have become a hot topic of discussion and are constantly changing. Not only by Muslims but also by non-Muslims are fascinated by this issue. The coverage of foreign (Western) media that always corners Islam (not individuals in Islam) and global terror events is very effective in changing a country’s policy to fight against Islam. However, this does not mean that they (the West) are discriminatory actions against Muslims living there. This study aims to review migration events and how the conditions of Muslim immigrants are in Bali and several essential countries in Europe and Asia. This article is a library research and empirical facts were obtained from various current and reliable news sources. This research examines the extent of the fate of Muslim immigrants in multiple countries with different characters and critically examines how the policies of these countries impact Muslim minorities. In addition, a comparative study was also conducted on the condition of Muslim immigrants being minorities in several countries with different backgrounds and characters. The results of research are: Firstly, Western countries highly uphold human rights. Some of the friction occuring with the Muslim minority is a precautionary measure, rather than discrimination as it is often presented to them. Secondly, the conflict between Muslim minority and local population is motivated by two factors: (a) their ignorance of the real Islam and thinking that terrorist Islam is the same as King Salman in Saudi Arabia or Imām Khumaeni in Iran, and (b) improved security to protect the country and all of its people from acts of terrorism. Thirdly, discriminatory treatment occurs in the East World, China, Myanmar, Thailand are real examples that until now have not received a solution; even the United Nations has stated that the Rohingya are the most oppressed minority on earth. This study contributes to academic discourse by offering a nuanced understanding of migration and the treatment of Muslim minorities across diverse geopolitical contexts.